Depositional Environment of the Gercus Formation in Jabal Haibat Sultan, NE Iraq; New Sedimentological Approach - Al-Mashaikie, Sa'ad; Al-Azzawi, Abbas; Kadum, Ali (Iraqi Journal of Science, 2023)
Sedimentary structures of Gercus Formation in NE Iraq was little studied in the last decades. In this study the identified sedimentary structures display alternative graded and fining upward cycles, load and flute casts, submarine channels, sand and clay balls and pillow structures, convolute and slump beddings, of marine turbidity origin. The foreland part of Tethys basin characterized by deep marine Tanjero and Kolosh Formations followed by the Gercus formation with conformable relationships. The Eocene aged Flysch comprises predominantly litharenitic sandstones and interbedded mudstones, both of turbiditic affinities and most likely derived from a NE Arabian Plate source. The sediments provide excellent examples of distal fan sands associated with turbidites and related sedimentary structures. The overall sedimentological characteristics of the examined section indicate that the sandstones were deposited in larger channel complexes that fed a mud-dominated slope. The more proximal sediments have a proportion of pebble conglomerates, shale-clast conglomerates and thick-bedded structureless pebbly sandstones, deposited by high-density turbidity currents, debris flows and slumping. Otherwise, more distal or more uniform sand-rich source are dominated by thick-bedded and amalgamated structureless sandstones. The massive sands are thought to originate from the gradual aggradation of sediment beneath steady flows.In this paper, new sedimentological evidences prove for the first time that the Gercus Formation was deposited in gravity-flow regime in marine environment. This is supported with identified glauconite index mineral in some sandstone beds.